(untitled) (Isagoge - Journal of Humanities and Social Sciences, 2023)
Oh Holy Spirit, thank you for knocking on my door, entering my life and filling it with joy. Protect our walk, walk and carefully preserve what God has inspired! Isagoge Journal of Humanities and Social Sciences, in our beloved Brazil, with its magnificent editors, exceptional beings; With the gift of the person they have joined us in a dossier invitation, I have accepted in a responsible and very gratifying way, for this reason, I reiterate my thanks! The commitment that is presented to humanity is focused on planetary-complex decolonial essences of philosophy. It is vital to answer: the colonized philosophy? Yeah. Definitely. Planetarily, decoloniality refers to the process aimed at historically transcending modernity-postmodernity-coloniality; that is: the libertarian project to reconcile philosophy with liberation, thinking of the victims still buried in the century of technologies, in our sentiments and in Latin American philosophies; but also the African ones; and so the planetary ones; with the need for the planetary decoloniality-complexity dyad to encourage it to be liberating, to help the Earth as a homeland. Science-philosophy-theology transcend disjunctive thinking. It is an exercise that goes in scale and transcendence in my lines of research. With great joy giving honor, glory, honor and power to my Father God, the dossier entitled: Sentient-thinking Transphilosophy: Ecosophical Re-linkages in times of global coloniality is presented; for the benefit of humanity. The call has been exceptional, the scientific texts are linked and put together an epistemic fabric of real value that goes beyond the thematic axes. Researchers, with extraordinary eloquence, have attested to the maxim: liberation of philosophy in the light of planetary-complexity decoloniality.